You are on page 1of 7

# Deriving the trigonometric addition formulae

March 28, 2011

## First we will prove the basic addition formula:

cos(a b) = cos a cos b + sin a sin b
From this formula we can easily derive the others. Consider two points P
and Q lying on a unit circle, (see Figure 1). Then the co-ordinates of P and
Q can be expressed in terms of the angles made with the x axis, a and b.
From Figure 2, P has co-ordinates:
P : P (cos b, sin b)
and similarly Q has co-ordinates:
Q : Q(cos a, sin a)
The distance d between P and Q can be found in terms of the angles a and
b:
d2 = (cos a cos b)2 + (sin a sin b)2
expanding
d2 = cos2 a 2 cos a cos b + cos2 b + sin2 a 2 sin a sin b + sin2 b

using
cos2 x + sin2 x = 1
1

P
X

ab
a

b
x

## Figure 1: Points P and Q lie on a unit circle.

P : (cos b, sin b)
1

sin b

b
O

cos b
Figure 2: Co-ordinates of P in terms of angle b.

sin(a b)

ab
O

cos(a b)

## Figure 3: Right-angled triangle OQX.

we have
d2 = 2 2 cos a cos b 2 sin a sin b

(1)

## Now consider another way to find d. We drop a perpendicular line from Q

to the line OP to meet at X. Working with the right-angled triangle QXP
(in Figure 1), then
d2 = |QX|2 + |XP |2
since |OP | = 1 = |XP | = |1 OX|
d2 = h2 + |(1 OX)|2
and using the right-angled triangle OQX, (see Figure 3)
d2 = sin(a b)2 + (1 cos(a b))2
d2 = sin2 (a b) + 1 2 cos(a b) + cos(a b)2
giving
d2 = 2 2 cos(a b)
Equating (1) and (2) gives:
2 2 cos(a b) = 2 2 cos a cos b 2 sin a sin b
2 cos(a b) = 2 cos a cos b 2 sin a sin b

(2)

cos x
1
0
5

4 3 2 1 0
1

5
x

## Figure 4: cos x is an even function

finally giving
cos(a b) = cos a cos b + sin a sin b

(3)

## An even function is one such that

f (x) = f (x)
Such a function would be symmetric about the y axis. This means that the
graph remains unchanged after a reflection in the y-axis. The function cos x
is even (see Figure 4) and so
cos(x) = cos x
An odd function however has
f (x) = f (x)
This type of function has rotational symmetry about the origin. Such a
graph is the same after a rotation of 180 about the origin. From Figure 5,
we see that sin x is an odd function and thus
sin(x) = sin x
So now we are in a position to derive a formula for cos(a+b). In equation
3 we use an angle b for b giving
cos(a (b)) = cos a cos(b) + sin(a) sin(b)

sin x
1

0
4 3 2 1 0
1

5
x

## Figure 5: sin x is an odd function

using the even and odd ideas above we get
cos(a (b)) = cos a cos b sin a sin b

## but cos(a (b)) cos(a + b) so we have another formula

cos(a + b) = cos a cos b sin a sin b

(4)

Using equation 4, we can find an expansion for cos(2a), the double angle
formula.
cos(a + a) = cos a cos a sin a sin a
cos(a + a) = cos2 a sin2 a

Hence we have
cos(2a) = cos2 a sin2 a

(5)

Remembering that
cos2 a + sin2 a = 1
We have two more formulae for cos(2a) Substituting for sin2 a in equation 5
we have
cos(2a) = cos2 a sin2 a
cos(2a) = cos2 a (1 cos2 a)

giving
cos(2a) = 2 cos2 a 1
5

(6)

C
(90 )

## Figure 6: Complementary angles.

If we now substitute for cos2 a in equation 5 we have
cos(2a) = (1 sin2 a) sin2 a

giving
cos(2a) = 1 2 sin2 a

(7)

## Consider the right-angled triangle ABC (see figure 6). Here

sin =

a
b

and

c
b
Now the angle (90 ) is the complementary angle for since both add to
give 90 . Now the sine of the complementary angle
cos =

sin(90 ) =

c
b

## The sine of the complementary angle is called the complementary sine or

cosine and hence
cos = sin(90 )
We can see that also
sin = cos(90 )
6

Now we can derive a formula for sin(a + b). In equation 3 we use an angle
(90 a) for a giving
cos((90 a) b) = cos(90 a) cos b + sin(90 a) sin b
using the relationships for the complementary angles we get
cos((90 a) b) = sin a cos b + cos a sin b
but cos((90 a) b)) cos(90 (a + b)) so we have another formula
sin(a + b) = sin a cos b + cos a sin b

(8)

Now if we use our ideas about odd and even functions, then we can to derive
a formula for sin(a b). In equation 8 we use an angle (b) for b giving
sin(a + (b)) = sin a cos(b) + cos(a) sin(b)
using the even and odd ideas from before we get
sin(a + (b)) = sin a cos b cos a sin b
and so we have another formula
sin(a b) = sin a cos b cos a sin b

(9)

Using equation 8, we can find an expansion for sin(2a), the double angle
formula.
sin(a + a) = sin a cos a + sin a cos a
which simplifies to

(10)

## Where to go from here

Now that you feel comfortable with these trigonometric equations you should
try and derive them yourself, just starting with a blank sheet of paper. Then
you should try to derive the expansion formula for tan(a + b) using equation
8 and equation 4. You can also derive the formula for the tangent of the
double angle tan(2a) . Good luck!
7